The Public-Private Management Dichotomy and the Transformations in the Public Administration - Lara-Nuñez , Tatiana de Lourdes (2023)
The conceptual relevance of the dichotomy of the public-private administration is shown by the fact that the two aforementioned converge in the administration as a science, other specialties also emerging, such as the administration of the third sector. In the present article a bibliographic and comparative review of the meaning, differences and results in general form obtained by the public, private and mixed administration at a general level, and its implication also in the economy of the nations that apply it, was carried out. The existing differences between public and private administration are analyzed. The fundamental role of the public administration in its role as coordinator of all sectors of society to achieve economic development is highlighted with the support of instruments and strategies used in the sector. It is important for future studies to propose strategies and instruments to improve global socio-economic development in favor of all, but considering the specificities and needs of each country.